Preferences for Healthy Carryout Meals in Low-Income Neighborhoods of Baltimore City. Issue 2 (March 2013) - Jeffries, Jayne K.; Lee, Seung Hee; Frick, Kevin D.; Gittelsohn, Joel
Context . The nutrition environment is associated with risk of obesity and other diet-related chronic diseases. In Baltimore's low-income areas, carryouts (locally prepared–food sources that offer food "to go") are a common source of food, but they lack a variety of healthy options for purchase. Objective . To evaluate individuals' preferences of healthy combination meals sold at carryouts and to identify successful intervention methods to promote healthier foods in carryouts in low-income communities in Baltimore. Method. The study estimated the relationship between combinations of healthier entrées (turkey club, grilled chicken), beverages (diet coke, bottled water), side dishes (watermelon, side salad), price points ($5.00, $7.50), and labeling on consumers' combination meal decisions using a forced-choice conjoint analysis. Logistic regression analysis was used to determine how individuals value different features in combination meals sold in carryouts. Results . There was a statistically significant difference between customer preference for the two entrées, with a turkey club sandwich being preferred over a grilled chicken sandwich ( p = .02). Carryout customers ( n = 50) preferred water to diet soda ( p < .00). Conclusion . Results suggested specific foods to improve the bundling of healthy combination meals. The selection of preferred promotion foods is important in the success of environmental nutrition interventions.